ENHANCEMENT THE LEARNING OUTCOMES OF THREE DIMENSION SPACE WITH KOOPERATIVE LEARNING JIGSAW IN ELEMENTARY SCHOOL - Wahyuni, Sri; Ariani, Yetti; abidin, zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of the research is to describe enhancement the learning outcomes of three dimension space with cooperative learning Jigsaw in elementary school. The kind of the research is classroom action research that use qualitative and quantitative approache including planning, implementation, observation and reflection. The subject of this research are the teacher and 16 students of the fourth grade. The result of observation of RPP in first cycle is 81%, second cycle is 93%, teacher’s aspect in first cycle is 74%, second cycle is 96%, student’s aspect in first cycle is 75%, second cycle is 93%. Learning outcomes of student in first cycle is 70, second cycle is 88,13. In conclusion, cooperative learning Jigsaw can increase the student’s result in studying three dimension space.Keyword:   three dimension space, cooperative learning Jigsaw